Pengaruh Substitusi Tepung Beras dan Tepung Tapioka terhadap Karakteristik Kimia dan Organoleptik Keripik Bayam - Dahlan, Sakinah Ahyani; Bait, Yoyanda; Supu, Nur Zenab K.; Parumpa, Nuraidah Hi.Dg.; Olomia, Yayan; Botutihe, Dhea Detasya (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2023)
In this study, spinach chips were made with various ratios of rice flour and tapioca flour with 3 replications for each treatment. Based on the results of the study, the chemical characteristics of spinach chips including water content, free fatty acid content and vitamin C had different values ​​for each treatment. The lowest water content value is found in spinach chips with the addition of 100% rice flour, which is 5.05%. While vitamin C levels were almost in spinach chips for all treatments. Organoleptic characteristics of spinach chips included taste, color, texture and aroma. The spinach chips with 100% rice flour competition had the highest score on the measurable criteria, taste and color. While on the aroma criteria, the spinach chips that have the most preferred texture by the panelists are in the ratio of 30% rice flour and 70% tapioca flour. Keywords: Spinach, Chips, Rice Flour and Tapioca Flour